Photon-Only Molecular Motor with Reverse Temperature-Dependent Efficiency - Gerwien, Aaron; Mayer, Peter; Dube, Henry (Journal of the American Chemical Society, 2018)
Light-driven molecular motors are archetypal molecular machines and enable fast and efficient unidirectional motions under photoirradiation. Their common working mechanism contains thermal ratcheting steps leading to slowed-down and even halted directional movement at lower temperatures. In this work, an alternative type of molecular motor is presented, which operates without thermal ratcheting in the ground state. Instead, three consecutive and different photoreactions lead to a directional stepwise rotation of one molecular fragment with respect to the other. This motion is increased in speed and directionality at lower temperatures and at the same time allows a considerably larger fraction of the supplied photon energy to be used for performing work.
CRIS-Team Scopus Importer:2020-04-02